2006
DOI: 10.1291/hypres.29.523
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with Hypotensive Agents Affects the Impaired Relaxation of the Penile Corpus Cavernosum in Hypertensive Rats

Abstract: Treatment of erectile dysfunction (ED) in hypertensive subjects remains to be formally established. There is currently no standardized treatment for ED in hypertensive subjects. In this study, we tested our hypoth-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 23 publications
(32 reference statements)
3
10
0
Order By: Relevance
“…It has been also reported that treatment with another ARB irbesartan reduced the vascular and cavernosal oxidative stress, and improved the endothelial function of the corpus cavernosum in cholesterol-fed ApoE −/− mice with atherosclerosis (4). In another experimental study, treatment with amlodipine did not change the level of oxidative stress marker (thiobarbiuric acid reactive substance) in corpus cavernosum in the SHR (35). These data are in agreement with our study that treatment with ARBs reduces oxidative stress in the penile tissue.…”
Section: Enos and Nnos Mrnas In The Rat Penile Tissuessupporting
confidence: 92%
See 1 more Smart Citation
“…It has been also reported that treatment with another ARB irbesartan reduced the vascular and cavernosal oxidative stress, and improved the endothelial function of the corpus cavernosum in cholesterol-fed ApoE −/− mice with atherosclerosis (4). In another experimental study, treatment with amlodipine did not change the level of oxidative stress marker (thiobarbiuric acid reactive substance) in corpus cavernosum in the SHR (35). These data are in agreement with our study that treatment with ARBs reduces oxidative stress in the penile tissue.…”
Section: Enos and Nnos Mrnas In The Rat Penile Tissuessupporting
confidence: 92%
“…Additionally, it has been reported that nifedipine augments cGMP production through the activation of cardiac soluble guanylyl cyclase as a negative inotropic effect but does not affect the NOS expression (31). Furthermore, it has been demonstrated that treatment with amlodipine significantly increased nitrate/nitrite and cGMP level in the plasma and corpus cavernosum in the SHR (1,35). Taken together, nifedipine and other L-type calcium channel blockers may be able to increase cGMP production in the penis independently of NOS…”
Section: Enos and Nnos Mrnas In The Rat Penile Tissuesmentioning
confidence: 99%
“…Ushiyama et al. [32,33] showed that ED in hypertensive rats results from impairment of the relaxation evoked by neurogenic CO and NO. Shamloul and Wang [34] demonstrated an increased intracavernosal pressure response in hypertensive rats after chronic hemin treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The spontaneous treatment of hypertensive rats with amlodipine or imidapril for 4 weeks induced a relaxation increase in the response to EFS of the corpus cavernosum. 18 Treating hypercholesterolemic rats with irbesartan also improved endothelial function. 22 In clinical trials, preliminary data from several randomized and open studies have suggested that angiotensin type 1 receptor antagonists may be associated with improvement in sexual function.…”
Section: Discussionmentioning
confidence: 98%
“…Several investigational and clinical reports have suggested that some types of medication, including antihypertensive drugs, alpha-adrenergic blockers and hypolipidemic agents, can help treat ED. In vitro studies examining alpha-adrenergic blockers, 14,15 calcium channel blockers 16,17 and angiotensin-converting enzyme inhibitors 18 have shown direct relaxation or induced increased relaxation in response to electrical field stimulation (EFS). Angiotensin receptor blockers have also been shown to improve sexual function 19--21 in clinical trials and have improved endothelial function in hypercholesterolemic rats.…”
Section: Introductionmentioning
confidence: 99%